Characteristics and outcome of synchronous bilateral Wilms tumour in the SIOP WT 2001 study: report from the SIOP Renal Tumour Study Group (SIOP-RTSG) - Sudour-Bonnange, Hélène; van Tinteren, Harm; Ramírez-Villar, Gema L.; Godzinski, Jan; Irtan, Sabine; Gessler, Manfred; Chowdhury, Tanzina; Audry, Georges; Fuchs, Joerg; Powis, Mark; van de Ven, Cornelis P.; Okoye, Bruce; et al. (British journal of cancer, 2024)
Among patients with nephroblastoma, those with bilateral disease are a unique population where maximising tumour control must be balanced with preserving renal parenchyma. Methods: The SIOP 2001 protocol recommended surgery after neoadjuvant cycle(s) of Dactinomycin and Vincristine (AV) with response-adapted intensification, if needed. Adjuvant treatment was given based on the lesion with the worst histology. Results: Three hundred and twenty seven patients with stage V disease were evaluable: 174 had bilateral Wilms tumour (BWT), 101 unilateral WT and contralateral nephroblastomatosis (NB) and 52 bilateral nephroblastomatosis. In these three groups, the estimated 5y-EFS was 76.1%, 84.6%, and 74.9%, respectively. AV chemotherapy alone was the successful chemotherapy for 58.7% of all the patients and 65.6% of the non-metastatic patients. Among the 174 patients with BWT, 149 (88.2%) had at least one nephron-sparing surgery. Twenty of 61 bilateral stage I patients were treated with four-week AV postoperatively achieving 94.4% 5y-EFS. At last follow-up, 87% of patients had normal renal function. Conclusions: This study demonstrates that AV without anthracyclines is sufficient to achieve NSS and good survival in the majority of patients. For patients with bilateral stage I WT and intermediate risk histology, only four weeks adjuvant AV seems to be sufficient.